2019
DOI: 10.1002/jia2.25223
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐exposure prophylaxis initiation and adherence among Black men who have sex with men (MSM) in three US cities: results from the HPTN 073 study

Abstract: Introduction Randomized clinical trials have demonstrated the efficacy of antiretroviral pre‐exposure prophylaxis (Pr EP ) in preventing HIV acquisition among men who have sex with men ( MSM ). However, limited research has examined initiation and adherence to Pr EP among Black MSM ( BMSM ) in the United States ( US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 65 publications
3
88
2
Order By: Relevance
“…In What's PrEP?, higher monthly income was associated with lower peer navigator acceptability. Interestingly, the HPTN 073 study of PrEP uptake and adherence among Black MSM found that men with higher incomes had higher rates of PrEP adherence, suggesting that men with means may need limited or no help engaging with HIV prevention services [47]. In our study, having a regular medical provider was associated with lower peer navigator acceptability, although this factor was not significant in multivariable analysis.…”
Section: Discussioncontrasting
confidence: 68%
“…In What's PrEP?, higher monthly income was associated with lower peer navigator acceptability. Interestingly, the HPTN 073 study of PrEP uptake and adherence among Black MSM found that men with higher incomes had higher rates of PrEP adherence, suggesting that men with means may need limited or no help engaging with HIV prevention services [47]. In our study, having a regular medical provider was associated with lower peer navigator acceptability, although this factor was not significant in multivariable analysis.…”
Section: Discussioncontrasting
confidence: 68%
“…Interestingly, the HPTN 073 study of PrEP uptake and adherence among Black MSM found that men with higher incomes had higher rates of PrEP adherence, suggesting that men with means may need limited or no help engaging with HIV prevention services [46]. In our study, having a regular medical provider was associated with lower peer navigator acceptability, although this factor was not significant in multivariable analysis.…”
Section: Discussioncontrasting
confidence: 68%
“…Socio-economic factors and poor governmental policy remain major barriers to widespread implementation of pre-exposure prophylaxis in Africa. Although, other probable factors hindering the implementation of PrEP men (MSM) (7). According to a cross sectional study, preexposure prophylaxis (PrEP) can reduce HIV transmission risk for many gay, bisexual and other men who have sex with men (8).…”
Section: Barriers To the Implementation Of Prep For The Prevention Ofmentioning
confidence: 99%